Efektifitas Teknik Thought Stopping Untuk Mengurangi Pola Pikir Negative Mahasantri Ibnu Katsir 2 Jember - Fitriyah Fitriyah; Nasruliyah Hikmatul Maghfiroh; Wahid Suharmawan (Universitas Nusantara PGRI Kediri, 2024)
Negative thinking can hinder students’ self-confidence, motivation, and effort in achieving academic and personal goals. This study aimed to examine the effectiveness of the thought stopping technique in reducing negative thinking among students of Ibnu Katsir 2 Jember. This study used a quantitative experimental approach with an experimental group and a control group. The sample consisted of 14 students selected from a population of 32, then divided into two groups. Data were collected through a questionnaire and analyzed using normality, homogeneity, and Wilcoxon tests with SPSS. The findings showed that the data were normally distributed (Sig. = 0.110) and homogeneous (Sig. = 0.350). The Wilcoxon test in the experimental group showed Z = -2.375 and Asymp. Sig. (2-tailed) = 0.018, indicating a significant difference before and after treatment. The thought stopping technique was effective in reducing students’ negative thinking.